Fractured modernity : making of a middle class in colonial North India - Joshi, Sanjay. 1962- (New Delhi : New York ; Oxford University Press, 2001)
With special reference to Lucknow, India.
Machine generated contents note: ONE -- Creating a Public: Emergence of a Middle Class in Colonial Lucknow -- Two -- An Uneasy Sangam: Gender and the Contradictions of Middle-class -- Modernity -- THREE -- Publicizing Religiosity: Modernity, Religion, and the Middle Class -- FOUR -- Impermanent Idenitities: Limits of Middle-class Nationalisms -- CONCLUSION -- Reflections on Fractured Modernity -- Bibliography -- Index.
Includes bibliographical references (p. [188]-202) and index.
Keywords: Middle class -- India